New Callicarpa (Lamiaceae) taxa: Two species and a natural hybrid from Hahajima Island, Ogasawara Islands, Japan - Sugai, Kyoko; Setsuko, Suzuki; Hayama, Kayo; Kato, Hidetoshi (Phytotaxa, 2025)
Two newly identified species of Callicarpa (Lamiaceae), C. boninensis and C. hahajimensis, along with a new natural hybrid, C. × chibusensis, are described. All were identified on Hahajima Island in the Ogasawara Islands, Japan. A comprehensive key to Callicarpa taxa in the Ogasawara Islands is also provided. Callicarpa boninensis, morphologically most similar to C. subpubescens, is distinguished by persistent stellate hairs on mature leaves and elongated petioles. Callicarpa hahajimensis, resembling C. parvifolia in the Chichijima Islands, differs in having reduced stellate hair density on both leaf surfaces and thinner leaves. Callicarpa × chibusensis, considered a natural hybrid between C. subpubescens and C. boninensis, is characterized by intermediate stellate hair densities—higher than in C. subpubescens but lower than in C. boninensis—on both leaf surfaces, smaller leaves than those of C. subpubescens, and an earlier flowering phenology compared to C. boninensis.